Systematic review and meta-analysis of the clinical survival significance of Sialyl-Tn expression in histological tissues from cancer patients - Lugo, Roberto; Ávila-Nava, Azalia; García-Pérez, Rodrigo; Herrera-Escalante, Sarahí; De la Cruz-Acosta, Jocelyne; Gutiérrez-Solis, Ana Ligia (Translational Cancer Research, 2019)
Background: The expression of Sialyl-Tn (STn) has been associated with different mechanisms of cancer. Several studies using histological tissue samples from different types of cancer showed differences in the STn expression patterns, but few studies have explored the association between STn expression and decreased overall survival. Therefore, a comprehensive analysis of the clinical significance of STn in cancer patients was performed. Methods: A systematic review and meta-analysis were done of scientific articles published and available from different sources, including MEDLINE/PubMed, Web of Science, Cochrane Library and LILACS. Odds ratio (OR) was represented by the number of deaths during follow-up in positive-STn versus negative- STn patients. OR from each study was pooled and the results were presented in a forest plot. Results: Eleven articles were included in the systematic meta-analysis. The estimated OR of 3.26 (95% CI: 2.12–5.02) was obtained. Furthermore, subgroups studies of gastric cancer showed an OR of 3.74 (95% CI: 2.47–5.66) and other cancer types reported an OR of 2.92 (95% CI: 1.16–7.32). Conclusions: This study showed that survival time was significantly longer in patients with negative-STn tumors than in those with positive results.